Tracing Upper Waters in the Arctic Ocean - Jones, E. P.; Anderson, Leif G. (1992)
We report results from the 1987 F.S. Polarstern cruise to the Nansen Basin that begin to address questions regarding how global climate change might affect the Arctic. Before the effects of global change can be assessed, the sources of upper waters must be determined and their circulation patterns mapped. In surface water, total carbonate concentrations distinguish between a northern fresh water component, whose origin is river runoff, and a southern freshwater component, whose origin is sea ice meltwater. Below the surface layer, the halocline in the Nansen Basin has the same unique nitrate-oxygen characteristic, NO, as the lower halocline in more central regions. The earlier speculation that this water forms in the Barents-Kara Sea region is confirmed. We hypothesize that some of this water must flow east and north from this region to central regions, eventually following the Polar branch of the Transpolar Drift and exiting through Fram Strait. Some can be traced in a general way flowing west directly to Fram Strait where the Polar and Siberian branches meet and flow into the Norwegian-Greenland Sea. This article is from 'Proceedings of the International Conference on the Role of whe Polar Regions in Global Change Held in Fairbanks, Alaska on 11-15 June 1990. Volume 1', AD-A253 027, p340-346. See also Volume 2, AD-A253 028.